Preparation method of manganese-boron sludge biochar composite material and application of manganese-boron sludge biochar composite material in tetracycline removal

By loading manganese and boron on biochar, manganese-boron sludge biochar composite material is prepared, and persulfate is activated to remove tetracycline in water, which solves the problems of low removal efficiency and environmental pollution in the prior art, and achieves an efficient and environmentally friendly tetracycline removal effect.

CN119701932APending Publication Date: 2025-03-28SUZHOU UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411888900.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is less efficient when removing tetracycline in water, traditional methods have problems such as long removal time, high cost and environmental pollution, and commonly used metal catalysts have certain toxicity.

Method used

By loading the metal manganese on biochar as the activation center of potassium persulfate on biochar, the specific surface area of ​​the material is increased, the catalytic activity is improved, and boron is loaded on biochar to avoid agglomeration and mediate electron transfer, manganese-boron sludge biochar composite is prepared, and the activated persulfate is used to efficiently remove tetracycline in water.

Benefits of technology

The efficient removal of tetracycline in the aqueous solution is achieved, with the removal rate reaching 95.6%, while avoiding the toxicity problem of metal catalysts, reducing costs, and the method is environmentally friendly and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701932A_ABST
    Figure CN119701932A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a manganese-boron sludge biochar composite material and application of the manganese-boron sludge biochar composite material in tetracycline removal, and the preparation method comprises the following steps: step 1, putting municipal sludge into hydrochloric acid, standing for 4-8 hours, and then drying and crushing to obtain sludge powder; step 2, uniformly mixing and grinding 1-3 parts by mass of sludge powder and 1-3 parts by mass of manganese chloride; step 3, putting the mixture in the step 2 into a solution containing absolute ethyl alcohol, adding 1-3 parts of boric acid powder, and ultrasonically mixing uniformly; heating in a water bath under a stirring condition to evaporate absolute ethyl alcohol, and then drying; step 4, heating the dried material to 750-850 DEG C in a tubular furnace in a nitrogen atmosphere at a rate of 8-12 DEG C / min, and keeping the temperature for 1-3 hours; and step 5, after cooling, washing with deionized water for multiple times, and drying to obtain a manganese boron sludge biochar composite material finished product. According to the application, potassium peroxodisulfate is activated by the manganese-boron sludge biochar composite material prepared by the method, so that efficient removal of tetracycline in an aqueous solution is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biochar, and in particular to a method for preparing a manganese-boron sludge biochar composite material and an application thereof in removing tetracycline. Background Art

[0002] Tetracycline is one of the most widely used antibiotics, with the characteristics of stable structure and strong hydrophilicity. Since most tetracyclines cannot be metabolized by organisms, direct discharge into water bodies will cause organisms to produce drug-resistant genes. As tetracyclines are enriched in organisms, they will also pose a threat to biological health. Traditional removal methods include adsorption, flocculation, and biodegradation, but the removal efficiency is low and the removal time is long. Compared with these methods, the persulfate activation method in advanced oxidation technology is one of the fastest, most economical and environmentally friendly methods for removing organic pollutants. However, some commonly used metal catalysts themselves have certain toxicity, and metal catalysis alone is easy to pollute the water environment. At the same time, the cost of pure metal catalysts is also relatively high, and they are prone to aggregation in water, resulting in reduced catalytic activity.

[0003] At present, a large number of municipal sludge produced by sewage treatment plants has not been properly disposed of. In order to maximize the resource utilization of municipal sludge and reduce the generation of harmful waste, the sludge is pyrolyzed into sludge biochar. Biochar has good ion exchange capacity and is a good metal / non-metal carrier. It can be used as an efficient persulfate catalyst. Therefore, how to use biochar to activate persulfate to achieve efficient removal of tetracycline in water has become a technical problem that the applicant needs to solve urgently. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a manganese-boron sludge biochar composite material and its application in removing tetracycline. The present invention increases the specific surface area of ​​the material and improves the catalytic activity by loading metal manganese on biochar as the activation center of potassium persulfate; the present invention prevents biochar from agglomerating and mediates electron transfer by loading boron on biochar; thus, the manganese-boron sludge biochar composite material prepared by the present invention can activate persulfate to achieve efficient removal of tetracycline in aqueous solution.

[0005] The technical solution of the present invention is a method for preparing a manganese-boron sludge biochar composite material, comprising the following steps:

[0006] Step 1, taking municipal sludge, placing it in hydrochloric acid and letting it stand for 4-8 hours, then drying and crushing it to obtain sludge powder;

[0007] Step 2: Take 1-3 parts of sludge powder and 1-3 parts of manganese chloride according to the mass ratio, mix and grind evenly;

[0008] Step 3, placing the mixture in step 2 into a solution containing anhydrous ethanol, adding 1-3 parts of boric acid powder, and mixing evenly by ultrasonication; then heating in a water bath under stirring conditions to evaporate the anhydrous ethanol, and then drying;

[0009] Step 4, heating the dried product to 750-850°C at a rate of 8-12°C / min in a tube furnace under a nitrogen atmosphere, and keeping the temperature for 1-3h;

[0010] Step 5: After cooling, wash with deionized water for multiple times, and dry to obtain a finished manganese-boron sludge biochar composite material.

[0011] In the above-mentioned method for preparing the manganese-boron sludge biochar composite material, in step 1, the concentration of the hydrochloric acid is 3 mol / L, the standing time is 6 hours, the drying temperature is 60° C., and the size of the crushed material is 100 mesh sieve.

[0012] In the aforementioned method for preparing the manganese-boron sludge biochar composite material, the mass ratio of the sludge powder, manganese chloride and boric acid is 1:1:1.

[0013] In the aforementioned method for preparing the manganese-boron sludge biochar composite material, in step 3, the ultrasonic mixing time is 30 minutes, the water bath heating temperature is 60°C, the water bath heating time is 6-8 hours, and the drying method is to place it in an oven at 60°C for overnight drying.

[0014] In the aforementioned method for preparing the manganese-boron sludge biochar composite material, in step 4, the temperature is raised to 800° C. at a rate of 10° C. / min and kept warm for 2 hours.

[0015] The manganese-boron sludge biochar composite material prepared by the above-mentioned preparation method is used to activate persulfate by the manganese-boron sludge biochar composite material to achieve the removal of tetracycline in the aqueous solution.

[0016] In the above application, in 1 liter of aqueous solution, the added amount of the persulfate is 0.1-0.4 mmol / L, and the added amount of the manganese-boron sludge biochar composite material is 0.2 g / L.

[0017] In the above application, the pH of the aqueous solution is 3-9.

[0018] In the above application, the temperature of the aqueous solution is 15-35°C.

[0019] In the aforementioned application, the aqueous solution further contains a free radical quencher.

[0020] Compared with the prior art, the present invention realizes the utilization of resources by pyrolyzing sludge into sludge biochar. The present invention loads metal manganese on biochar as the activation center of potassium persulfate, increases the specific surface area of ​​the material, and improves the catalytic activity. The present invention avoids biochar agglomeration by loading boron on biochar, and the doping of non-metallic elements can effectively improve the reactivity of carbon materials to electron acceptors, mediate electron transfer, and enhance the persulfate activation of biochar. Among them, the reason why the present invention chooses to load boron is that it has a lower electronegativity and is easy to form a covalent bond with C atoms during the carbonization process, thereby increasing the electron transfer rate, increasing defect edges and active sites, and adjusting the electronic structure and chemical stability of the carbon surface. Thus, the metal and non-metal loaded on the biochar of the present invention can work together to produce more selective active species, and tetracycline in the aqueous solution can be efficiently removed after activating persulfate. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Figures (a) and (b) are the SEM image and EDS image of the manganese-boron sludge biochar composite material, respectively;

[0022] Figure 2 This is the infrared absorption spectrum of manganese-boron sludge biochar composite material;

[0023] Figure 3 is the X-ray diffraction pattern of manganese-boron sludge biochar composite material;

[0024] Figure 4 Figures (a) and (b) are N2 adsorption and desorption curves of manganese-boron sludge biochar composite materials, respectively;

[0025] Figure 5 This is a graph showing the effect of potassium persulfate activated by manganese-boron sludge biochar composite material on the removal of tetracycline in water;

[0026] Figure 6 The XPS Mn 2p spectra of manganese-boron sludge biochar composite materials, (a) before reaction, (b) after reaction;

[0027] Figure 7 The effect of different potassium persulfate addition amounts on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composites;

[0028] Figure 8 The effect of different initial pH on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composites;

[0029] Fig. 9 The effect of different reaction temperatures on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composites;

[0030] Fig.10The effects of different coexisting ions on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composites;

[0031] Fig.11 The effects of different free radical quenchers on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composites;

[0032] Fig.12 EPR test diagram of different active species of potassium persulfate activated by manganese-boron sludge biochar composite material, (a) SO4 - · and ·OH, (b) is ·O2 - , (c) is 1 O2;

[0033] Fig.13 Electrochemical CA diagram of manganese-boron sludge biochar composite material with the addition of potassium persulfate and tetracycline. DETAILED DESCRIPTION

[0034] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to limit the present invention.

[0035] The experimental equipment and models used in the present invention include scanning electron microscope (SEM, Quanta FEG 250), energy dispersive spectrometer (EDS), infrared spectrometer (Bruker INVENIO S), X-ray photoelectron spectroscopy (Thermo Scientific K-Alpha), X-ray diffractometer (Bruker D8 Advanced), specific surface area pore size analyzer (TriStarⅡPlus 3030), electron paramagnetic resonance spectroscopy (Bruker A300-10 / 12), and electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd. Model CHI604E).

[0036] Manganese chloride (MnCl2·4H2O), anhydrous ethanol (C2H6O), sodium hydroxide (NaOH), methanol (CH4O), acetonitrile (C2H3N), sodium chloride (NaCl), sodium carbonate (Na2CO3) and sodium bicarbonate (NaHCO3) used in the present invention were purchased from Adamas Reagent Co., Ltd. Boric acid (H3BO3), tetracycline (C 22 H 24 N2O8), p-benzoquinone (C6H4O2), furfuryl alcohol (C5H6O2), tert-butyl alcohol (C4H 10 O2), 5,5-dimethyl-1-pyrroline-N-oxide and 2,2,6,6-tetramethylpiperidine were purchased from Aladdin Biochemical Technology; dilute hydrochloric acid (HCl) and sodium nitrate (NaNO3) were purchased from Wuxi Zhanwang Chemical Reagent, and oxalic acid (H2C2O4) was purchased from Shanghai Leyan Reagent.

[0037] Example 1: A method for preparing a manganese-boron sludge biochar composite material. This example uses municipal sludge, manganese chloride, and boric acid as basic raw materials, and adopts a grinding method and an impregnation pyrolysis method to prepare a manganese-boron sludge biochar composite material, comprising the following steps:

[0038] Step 1: Take municipal sludge, put it into hydrochloric acid (3 mol / L), let it stand for 4 hours, dry it at 60°C, and grind it through a 100-mesh sieve to obtain sludge powder.

[0039] Step 2: Grind 2 g of sludge powder and 3 g of manganese chloride for 1 h until completely mixed.

[0040] Step 3: Place the mixture in 150 mL of anhydrous ethanol solution, add 2 g of boric acid powder, and mix evenly by ultrasonication for 30 min. Heat in a 60°C water bath for 6-8 h with stirring until the anhydrous ethanol is completely evaporated, and place in a 60°C oven for drying overnight.

[0041] Step 4: Place the dried material into a combustion boat, and heat the tube furnace to 850°C at a rate of 8°C / min under nitrogen flow, and then maintain the temperature for 2 hours.

[0042] Step 4: After cooling, wash with deionized water for three times, then put into a 60° C. oven for drying overnight, store in a dryer for later use, and obtain a manganese-boron sludge biochar composite material after drying.

[0043] Example 2: A method for preparing a manganese-boron sludge biochar composite material, comprising the following steps:

[0044] Step 1: Take municipal sludge, put it into hydrochloric acid (3 mol / L) and let it stand for 8 hours, dry it at 60°C, and grind it through a 100-mesh sieve to obtain sludge powder.

[0045] Step 2: Take 3g of sludge powder and 1g of manganese chloride and grind them for 1h until they are completely mixed.

[0046] Step 3: Place the mixture in 150 mL of anhydrous ethanol solution, add 1 g of boric acid powder, and mix evenly by ultrasonication for 30 min. Heat in a 60°C water bath for 6-8 h with stirring until the anhydrous ethanol is completely evaporated, and place in a 60°C oven for drying overnight.

[0047] Step 4: Place the dried material into a combustion boat, and heat the tube furnace to 750°C at a rate of 12°C / min under nitrogen flow, and maintain the temperature for 2 hours.

[0048] Step 4: After cooling, wash with deionized water for three times, then put into a 60° C. oven for drying overnight, store in a dryer for later use, and obtain a manganese-boron sludge biochar composite material after drying.

[0049] Example 3: A method for preparing a manganese-boron sludge biochar composite material, comprising the following steps:

[0050] Step 1: Take municipal sludge, put it into hydrochloric acid (3 mol / L), let it stand for 6 hours, dry it at 60°C, and grind it through a 100-mesh sieve to obtain sludge powder.

[0051] Step 2: Grind 2 g of sludge powder and 2 g of manganese chloride for 1 h until they are completely mixed.

[0052] Step 3: Place the mixture in 150 mL of anhydrous ethanol solution, add 2 g of boric acid powder, and mix evenly by ultrasonication for 30 min. Heat in a 60°C water bath for 6-8 h with stirring until the anhydrous ethanol is completely evaporated, and place in a 60°C oven for drying overnight.

[0053] Step 4: Place the dried material into a combustion boat, and heat the tube furnace to 800°C at a rate of 10°C / min under nitrogen conditions, and then maintain the temperature for 2 hours.

[0054] Step 4: After cooling, wash with deionized water for three times, then put into a 60° C. oven for drying overnight, store in a dryer for later use, and obtain a manganese-boron sludge biochar composite material after drying.

[0055] In this example, the obtained manganese-boron sludge biochar composite material was subjected to SEM-EDS, FTIR, XRD and specific surface area pore size analysis.

[0056] 1. SEM-EDS results analysis

[0057] The surface morphology and structure of the manganese-boron sludge biochar composite material (composite material or sludge biochar for short) can be observed and analyzed by SEM. The image results are shown in the attached Figure 1 (a). From the attached Figure 1 (a) shows that the manganese-boron sludge biochar composite material is uneven and has many pores, which are filled with particles, indicating that it has a large specific surface area and can provide more pollutant adsorption sites and potassium persulfate activation sites. EDS spectrum is attached Figure 1 (b) Attachment Figure 1 (b) It can be seen that the surface of biochar contains manganese and boron elements after EDS scanning, indicating that the synthesis was successful.

[0058] 2. FTIR result analysis

[0059] FTIR can be used to analyze the surface functional groups of composite materials. Figure 2 Observable at 1580cm -1 、1166cm -1 、1100cm -1 、561cm -1The absorption peaks are C=C / C=O stretching vibration peak in the aromatic ring, CB / BO / CO bond peak, Si-OC / COC stretching vibration peak and Mn-O bond peak, indicating that biochar is coupled with manganese and boron, and the main component of sludge biochar is silicon oxide.

[0060] 3. XRD results analysis

[0061] Attached Figure 3 The XRD spectrum of the composite material is consistent with the FTIR results. The main component of sludge biochar is SiO2. After grinding with manganese chloride, Mn2Al4Si5O 18 As shown in the previous SEM image, hexagonal manganese aluminum mineral appeared on the surface of the composite material. In addition, the (110) crystal plane of manganese dioxide (JCPDS) was also found at 21.8°, but no peaks of manganese oxide and manganese tetraoxide were found, probably because they were in an amorphous state.

[0062] 4. BET result analysis

[0063] Attached Figure 4 (a) and (b) are the N2 adsorption-desorption curves of the composite material, respectively. The composite material has an H3 type hysteresis loop, and the pores are mainly mesopores. Table 1 shows the structural characteristics of biochar. It is observed that the composite material has a large specific surface area, reaching 199.39 m 2 / g, the pore volume and average pore diameter are 0.2537cm 3 / g and 5.0894nm.

[0064] Table 1 Structural characteristics of biochar

[0065]

[0066] Example 4: This example provides an application of the manganese-boron sludge biochar composite material prepared in Example 3, and uses the manganese-boron sludge biochar composite material in Example 3 to activate potassium persulfate to achieve the removal of tetracycline in the aqueous solution.

[0067] The specific steps of this embodiment include:

[0068] 1. Preparation of tetracycline solutions of different concentrations;

[0069] 1.1. Weigh 200 mg of tetracycline solid and dissolve it in deionized water.

[0070] 1.2. Transfer to a 1L volumetric flask and make up to volume with deionized water.

[0071] 1.3. Transfer to a brown reagent bottle and place in the refrigerator for later use.

[0072] 2. Tetracycline removal experiment;

[0073] 2.1. Take a certain amount of tetracycline solution with adjusted pH and concentration into a 250 mL conical flask containing manganese-boron sludge biochar composite material and potassium persulfate, and place it on a magnetic stirrer (400 r / min) to react for a certain time.

[0074] 2.2. Take a certain amount of tetracycline solution with adjusted pH and concentration into a 250 mL conical flask containing biochar, and place it on a magnetic stirrer (400 r / min) to react for a certain period of time.

[0075] 2.3. Take a certain amount of tetracycline solution with adjusted pH and concentration into a 250mL conical flask containing potassium persulfate, and place it on a magnetic stirrer (400r / min) to react for a certain period of time.

[0076] 2.4. Take a certain amount of tetracycline solution with adjusted pH and concentration into a 250mL empty conical flask and place it on a magnetic stirrer (400r / min) to react for a certain period of time.

[0077] 2.5. Use a pipette to take a sample and dilute it, use a disposable syringe to draw it up and filter the sample through a 0.45 μm filter membrane into a liquid phase vial. Add 10 μL of methanol to end the reaction.

[0078] 2.6. The results were tested by high performance liquid chromatography, with the test wavelength at 367 nm and oxalic acid (0.1%) and acetonitrile as the mobile phase.

[0079] 2.7. All reagents required in the experiment were prepared with deionized water, the experimental reaction temperature was 25°C, the experimental solution volume was 100 mL, the biochar addition amount was 0.2 g / L, the initial pH of the solution was 5.0±0.1, and the potassium persulfate addition amount was 0.2 mmol / L.

[0080] The calculation formula of removal rate is as follows:

[0081]

[0082] Note: Where C0 is the initial concentration of tetracycline (mg / L), Ci is the concentration of tetracycline during the removal process (mg / L).

[0083] Next, this example analyzes the effect of the presence or absence of potassium persulfate on the removal of tetracycline from water by the composite material.

[0084] By attaching Figure 5 It can be seen that tetracycline will not decompose by itself within one hour, and it will not be removed even if potassium persulfate is added. When only the composite material is added without potassium persulfate, the adsorption and removal rate of tetracycline is about 40%, but after adding potassium persulfate, the removal rate can reach more than 90%.

[0085] Furthermore, XPS analysis was performed on the manganese-boron sludge biochar composite material before and after the reaction. Figure 6 This is the XPS analysis of Mn 2p before and after the reaction. Figure 6 (a) The main valence states of Mn in the composite material before the reaction are Mn(Ⅱ), Mn(Ⅲ) and Mn(Ⅳ). The peak near 641.2eV belongs to Mn(Ⅱ), and the peaks near 642.6eV and 644.49eV belong to Mn(Ⅲ) and Mn(Ⅳ). Figure 6 The Mn 2p spectrum of (b) shows that the relative content of Mn(II) decreased from 33% to 23.2%, while the relative content of Mn(III) increased from 44.6% to 50.5%, and Mn(IV) increased from 22.4% to 26.3%. This indicates that there is a conversion between Mn(II) to Mn(III) and Mn(IV) during the degradation of tetracycline by potassium persulfate.

[0086] Furthermore, this example tests and analyzes the effects of different environmental conditions on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composite materials.

[0087] The reaction constant calculation formula is as follows:

[0088]

[0089] Note: Where C0 is the initial concentration of tetracycline (mg / L), Ci is the concentration of tetracycline during the removal process (mg / L), k is the reaction constant, and t is the reaction time.

[0090] 1. Effect of different potassium persulfate addition amounts on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composite materials.

[0091] As attached Figure 7 As shown in the figure, when the amount of potassium persulfate added is 0.1mmol / L, the tetracycline removal rate is low; when it is increased to 0.2mmol / L, the degradation efficiency is significantly improved; when it reaches 0.3mmol / L, the removal efficiency is reduced, and excessive potassium persulfate will consume active oxidizing substances; when the amount of potassium persulfate added reaches 0.4mmol / L, high concentrations of potassium persulfate will increase the reaction rate, but high concentrations of potassium persulfate will increase the corrosiveness of the water body. From the perspective of environment and cost, the best amount of potassium persulfate added is 0.2mmol / L.

[0092] 2. Effect of different pH on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composite materials.

[0093] Attached Figure 8As shown, pH also has a significant effect on the removal of tetracycline. In the pH range of 3-7, the manganese-boron sludge biochar composite material has a high catalytic activity for potassium persulfate, and the removal rate under acidic conditions is higher than that under acidic or alkaline conditions. Under acidic conditions, the metal elements in the catalyst are easily leached, resulting in a reduction in the catalytic sites on the surface of the material; under alkaline conditions, the metal on the surface of the biochar is passivated to form an oxide layer, thereby limiting the contact reaction between the internal active sites and potassium persulfate, and at the same time, the low redox potential ·OH will quench SO4 - ·, and becomes the main active substance. Therefore, pH 5 is the best choice.

[0094] 3. Effect of different temperatures on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composite materials.

[0095] Attached Fig. 9 As shown in the figure, temperature has little effect on tetracycline removal. The removal rate of tetracycline is the highest at room temperature of 25℃, and the removal effect is slightly reduced at 15℃ and 35℃, so 25℃ is the appropriate treatment temperature.

[0096] 4. The effect of different coexisting ions on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composites.

[0097] Since the actual water body is relatively complex, the free radicals and non-free radicals generated in the system will be affected to varying degrees. Fig.10 Add NO3 as shown - , CI - 、HCO3 - The removal efficiency of tetracycline was slightly affected. These three anions would quench the free radicals generated in the system, resulting in a decrease in the removal efficiency. 2- The inhibitory effect is greater because CO3 2- After adding, it will selectively quench O2 - and ·OH. In addition, CO3 2- It will make the solution alkaline. Through the tetracycline removal experiment at different pH, it is known that the degradation efficiency of tetracycline is low at high pH, ​​while HCO3 - Adding HCO3 will make the solution neutral. - The addition of CO3 2- The inhibitory effect is low.

[0098] Furthermore, this example also tests the effect of different free radical quenchers on the removal of tetracycline by potassium persulfate activated by manganese-boron sludge biochar composite materials.

[0099] The quenching agents added in this example were all added before the reaction started, and methanol was added to quench OH and SO4 - ·, tert-butyl alcohol is added to quench ·OH, p-benzoquinone is added to quench ·O2- , furfuryl alcohol was added for quenching 1 O2; methanol and tert-butyl alcohol concentrations were 100mmol / L, and p-benzoquinone and furfuryl alcohol concentrations were 4mmol / L. EPR test: After 5 minutes of reaction, the filtrate was taken and 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) was added to detect OH, SO4 - · and · O2 - ; Add 2,2,6,6-tetramethylpiperidine (TEMP) for detection 1 O2.

[0100] Attached Fig.11 As shown in the figure, the addition of methanol has a certain inhibitory effect on the degradation of tetracycline, while the addition of tert-butyl alcohol has almost no inhibitory effect, indicating that SO4 - · plays a certain role, but ·OH does not exist. Using DMPO as a spin trap, Fig.12 (a) SO4 can be clearly seen in the EPR graph - · and ·OH signals may react on the catalyst surface to generate ·OH, but tert-butanol can only quench ·OH in the solution, so tert-butanol has no inhibitory effect. The degradation rate was reduced by 30% after the addition of benzoquinone. Fig.12 (b) shows that after adding DMPO, obvious DMPO-·O2 - peak, indicating that O2 - It has a certain contribution to the degradation of tetracycline. FA has a certain inhibitory effect after addition, inhibiting about 16%. Fig.12 (c) shows that TEMP- 1 O2 peak.

[0101] Furthermore, this embodiment also conducted a current change test when potassium persulfate and tetracycline were added to the manganese-boron sludge biochar composite material.

[0102] A three-electrode system was used, with the working electrode being a glassy carbon electrode coated with a composite material, the counter electrode being a platinum electrode, the reference electrode being an Ag / AgCl electrode, and the electrolyte being 50mmol / L Na2SO4. The chronoamperometric test (CA) was performed by injecting potassium persulfate at 200s and tetracycline solution at 400s to detect the current change.

[0103] As attached Fig.12 As shown, after potassium persulfate was added at 200s, the current changed and a positive current peak appeared immediately. Electrons were transferred from the manganese-boron sludge-biochar composite material to potassium persulfate. There was a strong negative current peak when tetracycline solution was injected at 300s, which means that electrons were transferred from tetracycline to the manganese-boron sludge-biochar composite material. These phenomena collectively indicate that the manganese-boron sludge-biochar composite material not only acts as a catalyst to catalyze potassium persulfate to produce free radicals, but also acts as an "electron bridge" to promote electron transfer.

[0104] In summary, the manganese-boron sludge biochar composite material prepared by the present invention is an environmentally friendly material for removing tetracycline antibiotics in water. The experimental results show that the manganese-boron sludge biochar composite material can achieve a tetracycline removal rate of 95.6% under the conditions of reaction temperature of 25°C, reaction time of 1h, initial pH=5, manganese-boron sludge biochar composite material dosage of 0.2g / L, and potassium persulfate addition of 0.2mmol / L, and has a wide range of applications. During the removal process, manganese is added to the biochar to increase the specific surface area, serving as the catalytic active center of potassium persulfate to produce active substances; boron is added to avoid biochar agglomeration, adjust the surface electronic structure, and mediate electron transfer; the manganese-boron sludge biochar composite material can activate potassium persulfate to produce SO4 - ·、·OH、·O2 - and 1 O2 oxidizes tetracycline and can also mediate electron transfer, leading to the degradation of tetracycline.

[0105] The above embodiments only express the implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a manganese-boron sludge biochar composite material, characterized in that: The steps include: Step 1, taking municipal sludge, placing it in hydrochloric acid and letting it stand for 4-8 hours, then drying and crushing it to obtain sludge powder; Step 2: Take 1-3 parts of sludge powder and 1-3 parts of manganese chloride according to the mass ratio, mix and grind evenly; Step 3, placing the mixture in step 2 into a solution containing anhydrous ethanol, adding 1-3 parts of boric acid powder, and mixing evenly by ultrasonication; then heating in a water bath under stirring conditions to evaporate the anhydrous ethanol, and then drying; Step 4, heating the dried product to 750-850°C at a rate of 8-12°C / min in a tube furnace under a nitrogen atmosphere, and keeping the temperature for 1-3h; Step 5: After cooling, wash with deionized water for multiple times, and dry to obtain a finished manganese-boron sludge biochar composite material.

2. The method for preparing the manganese-boron sludge biochar composite material according to claim 1, characterized in that: In step 1, the concentration of the hydrochloric acid is 3 mol / L, the standing time is 6 h, the drying temperature is 60° C., and the size of the pulverized product is 100 mesh sieve.

3. The method for preparing the manganese-boron sludge biochar composite material according to claim 1, characterized in that: The mass ratio of the sludge powder, manganese chloride and boric acid is 1:1:

1.

4. The method for preparing the manganese-boron sludge biochar composite material according to claim 1, characterized in that: In step 3, the ultrasonic mixing time is 30 minutes, the water bath heating temperature is 60° C., the water bath heating time is 6-8 hours, and the drying method is to place in an oven at 60° C. for overnight drying.

5. The method for preparing the manganese-boron sludge biochar composite material according to claim 1, characterized in that: In step 4, the temperature is raised to 800°C at a rate of 10°C / min and kept at this temperature for 2h.

6. Application of the manganese-boron sludge biochar composite material prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The removal of tetracycline from aqueous solution was achieved by activating persulfate using manganese-boron sludge biochar composite material.

7. The use according to claim 6, characterized in that: In 1 liter of aqueous solution, the added amount of the persulfate is 0.1-0.4 mmol / L, and the added amount of the manganese-boron sludge biochar composite material is 0.2 g / L.

8. The use according to claim 6, characterized in that: The pH of the aqueous solution is 3-9.

9. The use according to claim 6, characterized in that: The temperature of the aqueous solution is 15-35°C.

10. The use according to claim 6, characterized in that: A free radical quencher is also added to the aqueous solution.

Citation Information

Cited By

  • Magnetic iron-based catalyst based on sludge alginate as well as preparation method and device of magnetic iron-based catalyst

    CN121130893A